The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1532-950x.2007.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

Tibial Osteotomies for Cranial Cruciate Ligament Insufficiency in Dogs

Abstract: Limb function in dogs with CrCL insufficiency can be improved using the currently described tibial osteotomy techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
203
1
44

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(256 citation statements)
references
References 71 publications
8
203
1
44
Order By: Relevance
“…Veterinary medicine has reported the beneficial results of high tibial osteotomy in several animal studies [26]; however, outcomes in human models have been more limited. Harner et al reported their biomechanical results of changing tibial slope in a human cadaveric model and found that increasing tibial slope does not affect AP translation or in situ forces on the ACL, but did result in anterior positioning of the tibia.…”
Section: Outcomes For Malalignment With Instabilitymentioning
confidence: 99%
“…Veterinary medicine has reported the beneficial results of high tibial osteotomy in several animal studies [26]; however, outcomes in human models have been more limited. Harner et al reported their biomechanical results of changing tibial slope in a human cadaveric model and found that increasing tibial slope does not affect AP translation or in situ forces on the ACL, but did result in anterior positioning of the tibia.…”
Section: Outcomes For Malalignment With Instabilitymentioning
confidence: 99%
“…Elas promovem estabilidade funcional do joelho durante a fase do passo, reduzem o deslocamento de translação cranial da tíbia, conforme novo conceito de tratamento, que preconiza estabilidade dinâmica, alterando a geometria óssea da articulação (Kim et al, 2008). Para a escolha do melhor tratamento da RLCCr, em cães, dentro das técnicas de osteotomias corretivas, a mensuração do ângulo do platô tibial (APT) é um importante componente a ser determinado (Reif et al, 2004).…”
Section: Introductionunclassified
“…O sucesso da técnica de ATT em reduzir ou eliminar as forças de deslocamento cranial da tíbia em joelhos de cães com RLCCr tem sido documentado em estudos experimentais (Apelt et al, 2007;Kim et al, 2008Kim et al, /2009Guerrero et al, 2009) e em estudos clínicos publicados recentemente (Hoffmann et al, 2006;Lafaver et al, 2007;Voss et al, 2008;Kemper et al, 2011;Steinberg et al, 2011;Wolf et al, 2012).…”
Section: Introductionunclassified